A mixed effects negative binomial analysis of road mortality determinants in Sub-Saharan African countries. (January 2018) - Soro, Wonmongo Lacina; Wayoro, Didier
Highlights: Sub-Saharan Africa has the world highest road mortality rate. Seat belts laws are still ineffective to curb traffic fatalities in Sub-Saharan Africa. Random breath tests are an effective policy to curb traffic fatalities in Sub-Saharan Africa. There is an increasing trend in traffic fatalities in Sub-Saharan Africa. Abstract: This paper uses aggregate data for a panel of 23 Sub-Saharan African countries to explore the potential predictors of road traffic fatalities between 2001 and 2010. In addition to the Gross Domestic Product per capita, the set of covariates includes some demographic, safe driving behavior, health and infrastructure-related variables. Estimations from a mixed effects negative binomial regression suggest that the fraction of populations aged between 15 and 64 years, the size of the road network and seat belt laws significantly increase fatalities. However, populations of age 65 and above, hospital beds and physicians' densities, and road audits significantly decrease these fatalities. Moreover, traffic fatalities are found to increase with the Gross Domestic Product per capita. The economic implications of this finding is not to lower the economic growth but to design policies and technologies that could prevent African countries from experiencing the same road tragedy observed in industrialized countries during their development process.